Identifikasi Tumbuhan Obat yang Dimanfaatkan Masyarakat Suku Kaili di Desa Sipi Kecamatan Sirenja - Fadilah, Nur; Nurdin, Musdalifah; Isnainar, Isnainar; Febriawan, Aan; Mawaddah, Hayyatun; Lilies, Lilies (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify the types of medicinal plants, parts of medicinal plants and the processing of medicinal plants used by the Kaili Tribe in Sipi Village, Sirenja District, Donggala Regency, Central Sulawesi. The type of research used in this study is descriptive qualitative with the snowball sampling method. The sampling technique used the roaming method and free collection. The method of determining the sampling area using the roaming method of the research location, namely, explored from the initial boundary of hamlet 1 in the west to the boundary of hamlet 4 in the east in Sipi Village. Data were collected through field observations, free interviews with people who have local knowledge about medicinal plants, and direct documentation. The results showed that there are 20 species of medicinal plants from 12 families that are used to treat various diseases such as diabetes, external wounds, tinea versicolor, toothache, digestive disorders, and others. The plant parts used include roots/rhizomes, stems, leaves and sap. The methods of utilization are various such as boiling, pounding, rubbing, chewing and drops. This research shows the importance of preserving traditional knowledge regarding the use of medicinal plants by local communities as part of local wisdom that is passed down from generation to generation.